Optimal settings for the Holmium: YAG laser in pediatric endourology: Tips and tricks. Issue 2 (April 2020) - Faure, Alice; Boissier, Romain
Summary: Introduction: To the best of our knowledge, no pediatric paper has been published regarding specifically how to set the Holmium:YAG laser for multiple urologic applications. Objective: To provide insight into the laser parameters for pediatric applications. Study design: We describe the principle and the settings of the laser. Results: The Holmium:YAG laser can produce four different biological effects: (1) fragmentation of stones in small fragments that can be retrieved with grasping instruments, thereby increasing the immediate stone-free outcome. For fragmentation lithotripsy, the laser has to be set with a high energy, low frequency and short pulse duration; (2) dusting which produces fine dust that can spontaneously evacuate, avoiding the use of basket retrieval. The dusting setting requires low energy, high frequency and long pulse duration; (3) incision of posterior urethral valves or ureterocele when all settings are maximized: high energy, high frequency and long pulse duration; (4) coagulation of urothelial tumors using high frequency, long pulse duration and slightly lower energy than required for incision. Discussion: Both dusting by painting and fragmentation with retrieval for ureteroscopic laser lithotripsy are effective. Although dusting tends to be associated with shorter operative times and a lower risk of ureteral trauma, this approach has a potential risk of recurrent stone formation from dust failing to pass. In contrast, fragmentation with extraction may provide for a more immediate postoperative stone-free result. Altering the pulse energy, frequency, width and modulation can help to optimize lithotripsy efficiency. Lower pulse energy settings result in smaller fragments, less retropulsion and reduce fiber tip degradation. A shallow depth of penetration in water and tissue allows precise energy application and provides a margin of safety. Conclusion: An understanding of Ho-YAG laser settings will permit the pediatric surgeon to make a better use of the device for different urological applications. Figure Summary Laser settings for pediatric endourology. Figure Summary